Is chronic hypoxemia in patients with chronic obstructive pulmonary disease associated with more marked nutritional deficiency?: A study of the fat-free mass evaluated by anthropometry and bioelectrical impedance methods - Godoy, I. [UNESP]; Castro, M. H. [UNESP]; Silva, E. [UNESP]; Togashi, R. H. [UNESP]; Geraldo, R. R C [UNESP]; Campana, A. O. [UNESP] (My University, 2000)
In order to determine wheter blood gases abnormalities, specially hypoxemia, are associated with more marked changes in fat-free mass in patients with chronic obstructive pulmonary disease (CPOD), nutritional assessment was performed on 16 normoxemic (PaO 2 > 55 mm Hg) and 16 hypoxemic (PaO 2 < 55 mm Hg) COPD patients in stable clinical condition. Body weight was expressed as percentage of the ideal body weight. Fat-free mass was estimated by anthropometry (FFM-Anthr) and by bioelectrical impedance (FFM- BI). Handgrip-strength was assessed as a measure of peripheral skeletal muscle strength. Patients were age-matched and presented similar degree of airway obstruction. Malnutrition, defined as body weight less than 90% of the ideal, was observed in 19% of the normoxemic patients and in 25% of the hypoxemic patients (p>0,05). FFM values in hypoxemic patients, estimated by both methods, were not different from those observed in normoxemic patients. No significant difference was observed on handgrip values between the two groups. No correlation was found between nutritional indices and pulmonary function and gases exchange parameters. FFM correlated positively with values of peripheral muscle function in normoxemic and hypoxemic patients. These data add further evidence to the hypothesis that hypoxemia is not a primary cause of the nutritional deficiency observed in COPD patients.
Keywords: Anthropometry; Bioelectrical impedance; Chronic obstructive pulmonary disease; Fat-free mass; Hypoxemia; Nutritional deficiency; adult; aged; analytic method; anthropometry; bioenergy; blood gas analysis; body composition; chronic obstructive lung disease; clinical article; female; grip strength; hand grip; human; hypoxemia; impedance; lung function; male; malnutrition; muscle strength; nutritional deficiency; priority journal; skeletal muscle; Aged; Anoxemia; Body Composition; Electric Impedance; Female; Humans; Lung Diseases, Obstructive; Male; Middle Aged; Nutrition Assessment; Nutrition Disorders; Nutritional Status; Prevalence; Prognosis; Pulmonary Gas Exchange; Risk Factors